(untitled) (The Research of Medical Science Review, 2025)
Background: Early-onset neonatal sepsis (EONS) is a significant cause of morbidity and mortality in neonates, particularly in those born to mothers with premature rupture of membranes (PROM). The frequency and risk factors associated with EONS in this population are not well established in Pakistan. Study setting and Duration: This study was conducted at NICU of Combined Military Hospital Lahore, Pakistan, from 4th Jan 2025 to 4th April 2025. Study design: The study employed a cross-sectional design to investigate the frequency and risk factors associated with EONS in neonates born to mothers with PROM ≥18 hours. Methodology: The study included 150 neonates born to mothers with PROM of ≥18 hours, with a gestational age of more than 28 weeks. Neonates with congenital anomalies, those receiving empiric antibiotics before septic workup, and pregnancies complicated by maternal comorbidities were excluded. Data were collected using a structured proforma, and statistical analysis was performed using SPSS version 26. Results: The frequency of EONS in the study population was 12%. Preterm birth (p = 0.02) and birth weight < 2000 grams (p < 0.05) were identified as significant risk factors for developing EONS. The most common pathogens isolated from blood cultures were Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae. Conclusion: This study highlights the importance of early recognition and treatment of EONS in neonates born to mothers with PROM, with preterm birth and low birth weight being significant risk factors for developing EONS in these neonates.